PERAN PEMERINTAH DALAM PENGEMBANGAN PARIWISATA DI DESA COMPONG KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Ilmi, Nur; Dema, Herman; Syarifuddin, Haeruddin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Compong Village, which is located in Pitu Riase District, Sidenreng Regency, is one of the villages in Indonesia that has begun to develop waterfall tourism objects. This paper will analyze the development of waterfall tourism objects or ATP (Pattumba Waterfall) which began to be developed from 2018 to 2022 with research questions about the government's role and strategy in developing the Pattumba waterfall tourism sector and also to find out the factors that influence the development of the tourism sector. Pattumba waterfall. This paper uses a quantitative descriptive research method. Data collection techniques used observation, literature review and questionnaires with data analysis using SPSS26. Determination of informants in this study using a purposive sampling method. The results of this study indicate that the Government's role and strategy in developing the Pattumba Waterfall tourism sector in Compong Village, Pitu Riase District, Sidenreng Rappang Regency as measured through indicators of inspiration, facilitators, and intermediaries showed very good results with a percentage of 82.53%, and factors that influencing tourism development in Compong Village, Pitu Riase District, Sidenreng Rappang Regency, namely, Tourist attractions, 55%, Accessibility, 78.6%, Infrastructure, 79.2%, Accommodation and Sapta Pesona, 83%. Based on these factors, it shows that the factors that most influence the development of Pattumba Waterfall are accommodation and Sapta Pesona with a percentage of 83%.